Analysis of whole cell protein profiles by SDS-PAGE to identify indigenous cellulose-producer acetic acid bacteria - Sarkono Sarkono; Soekarti Moeljopawiro; Bambang Setiaji; Langkah Sembiring (Universitas Gadjah Mada, 2016)
This study was carried out to analyze the suitability of the identification of four indigenous cellulose-producing acetic acid bacterial isolates (ANG29, KRE65, ANG32 and SAL53) based on the analysis of whole cellular protein profiles against identification based on phenotypic traits. Whole cellular protein profiles were determined by sodium dodecyl sulfate-polyacrylamide gel electrophoresis (SDS-PAGE) method. The whole cellular protein profiles obtained from sample isolates, were compared with reference isolates for species identification. The results showed that based on visual observations can be determined as much as 12 bands of protein with a molecular weight of 19,099 KDa up to 132.182 KDa. Based on the analysis of protein bands were detected visually, fourth indigenous cellulose- producing acetic acid bacterial isolates in the study had a higher similarity profile to the reference strain Gluconacetobacter xylinus BTCC 769 compared with other reference strains namely G. hansenii NBRC 14820T. This condition is consistent with the results of the identification of fourth cellulose producing acetic acid bacterial isolates based on phenotypic traits. Thus, the whole cellular protein profiles by SDS-PAGE technique can be used as a one of method to identification of cellulose producing acetic acid bacterial isolates.